Students' Perspective on the Use of Quizizz Android-Based Application as an Assessment Tool for Arabic Language Learning - Yusuf Muhtarom; Muhajir, Muhajir; Imam Muchsin (INGGARA (Jurnal Pendidikan Bahasa Inggris dan Bahasa Arab), 2023)
This study aims to describe student responses regarding the use of Quizizz as an alternative media in Arabic language learning. This study used a descriptive research method. The subjects of this study were students of Islamic Cultural History, Faculty of Adab and Culture, Sunan Kalijaga State Islamic University who took Arabic courses during the 2021/2022 academic year. This study employed a questionnaire instrument to collect research data. The data were obtained by distributing questionnaires to students of the Islamic Cultural History program through Google Form. The results revealed both positive and negative responses related to the implementation of tests using Quizizz as an assessment media. With the use of Quizizz for assessments, 90.9% of students reported taking tests independently. Students generally found the application of Quizizz in their lectures to be enjoyable and moderately challenging. However, some students expressed concerns that Quizizz does not allow for reviewing answers and highlighted the vulnerability of Quizizz usage, particularly for students in remote areas with poor internet connectivity.